Urban Poverty and Primary Education Sustainability Access: The Influence of Parental Income in Nairobi Informal Settlements, Kenya - Oketch David Owuor; Milkah Ajuoga; Antony Wando Odek (Research Parks Publishers, 2026)
Children residing in urban informal settlements continue to have differing levels and access to education services despite the free primary education program and policies to support children’s transition to school within Kenya. This study examines how parental income impacts the ability of children, living in three informal settlements (Kibera, Mathare and Korogocho), to gain access to primary education. Using a mixed methods approach, the study analyzed survey data from 347 respondents, 11 interviews and nine focus groups, and the findings supported Educational Productivity Theory and Classical Liberal Theory of Equal Opportunity. The results of the study indicated that having adequate school materials positively impacted the children’s attendance and accessibility to school (β = 0.35). Poverty negatively impacted children’s access to education (β = 0.25). There was a moderate association between unemployment and psychosocial factors, giving a moderate association (β = 0.16, p = 0.031). A connection also existed between job losses and psychosocial factors. From qualitative data from the participants, one can conclude that parents struggle to satisfy their children’s educational requirements like buying school uniform and ensuring they have something to eat. The current study indicates that family material and financial resources are positively associated with educational opportunities for children.